2020
DOI: 10.1007/s11012-019-01122-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-standard and constitutive boundary conditions in nonlocal strain gradient elasticity

Abstract: Zaera et al. (Int J Eng Sci 138:65-81, 2019) recently showed that the nonlocal strain gradient theory (NSGT) is not consistent when it is applied to finite solids, since all boundary conditions associated to the corresponding problems cannot be simultaneously satisfied. Given the large number of works using the NSGT being currently published in the field of generalized continuum mechanics, it is pertinent to evince the shortcomings of the application of this theory. Some authors solved the problem omitting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…It is beneficial to point that as a diverse common continuum theory, the NSGT in differential state is yielded from the conversion of strain gradient, in integral form, to a differential equation, and it has been widely hired with neglecting imperative constitutive boundary conditions (CBCs) resulted from this transformation. According to this verifiable truth, the incongruity of the NSGT has been recently affirmed [86,87], so that it has been showed and proved that the order of the NSGT equations are less than the number of all imperative boundary conditions. Because of these uncertainties about the NSGT along with paradox of the differential state of nonlocal theory, in this paper, the two-phase local/nonlocal theory is appointed to take the size effects.…”
Section: Introductionmentioning
confidence: 89%
“…It is beneficial to point that as a diverse common continuum theory, the NSGT in differential state is yielded from the conversion of strain gradient, in integral form, to a differential equation, and it has been widely hired with neglecting imperative constitutive boundary conditions (CBCs) resulted from this transformation. According to this verifiable truth, the incongruity of the NSGT has been recently affirmed [86,87], so that it has been showed and proved that the order of the NSGT equations are less than the number of all imperative boundary conditions. Because of these uncertainties about the NSGT along with paradox of the differential state of nonlocal theory, in this paper, the two-phase local/nonlocal theory is appointed to take the size effects.…”
Section: Introductionmentioning
confidence: 89%
“…It was found that the bending, as well as shear components associated with the radial displacement, were considered as the increasing functions of the angle of the nanobeam. Nonlocal strain-gradient model behavior of nano-structures with consideration of non-standard as well as constitutive boundary conditions was scrutinized by Zaera et al [474]. They revealed that the obtained solution did not comply with energy conservation.…”
Section: Linear Static Bending Of Micro/nano-structuresmentioning
confidence: 99%
“…xx 1 are the classical and higher-order stresses, respectively. Based on Lim's theory, the final constitutive equation of the nonlocal strain-gradient model can be proposed as [69][70][71][72][73][74][75][76][77][78][79]:…”
Section: Nonlocal Strain-gradient Continuum Mechanics Theorymentioning
confidence: 99%